Assessing students’ self-efficacy when solve mathematical problem based on gender - Syamsu Alam; Mega Teguh Budiarto; Tatag Yuli Eko Siswono (International Journal of Trends in Mathematics Education Research, 2022)
Self-efficacy, problem solving, and gender differences are aspects that many researchers concern to today. Therefore, the purpose of this study was to describe the profile of students’ self-efficacy in solving problems based on gender. We used a qualitative approach with exploratory research to answer the research objectives. We used the Mathematical Ability Test (TKM) instrument, Mathematical Problem-Solving Tasks (TPMM), and interview guidelines to consider the selected subjects. Next, two students were selected (14 years old, of different gender, and had good math skills) to participate in the study. Data from transcripts and student work were used to perform data analysis. The results revealed that there were fundamental differences between the two subjects based on three dimensions of self-efficacy (magnitude, strength, and generality). This is discussed further in this article. Finally, we suggest to explore the influence of regional culture on students’ self-efficacy in the classroom.